Preliminary study on congenital anomaly in DR. Sardjito General Hospital Yogyakarta - Romi, M. Mansyur (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: Congenital anomalies and genetic diseases tend to increase and dominate hospital admittance,especially in the pediatric wards in developed countries. The spectrum of diseases in regions with lowinfant mortality rate is likely to go with such tendency It is necessary to study congenital anomalies andgenetic diseases at Dr. Sardjito General Hospital, locating in a region with much lower infant mortalityrate than that of the national average.Objective: To know the occurrence of congenital anomalies and its pattern among DR. Sardjito GeneralHospital in-patients.Method: An desricptive study was done on secondary data taken from data-base of the Hospital in 1998 â2002 period. All of admittances in that period diagnosed as primary or secondary diagnosis, with Q00 âQ99 congenital malformations, deformations, and chromosomal abnormalities according to InternationalClassisifaction of Diseases (ICD), were included. The pattern of anomaly at the Hospital was compared tothat of different population and period.Results: There were 1968 1070 males and 898 females) admittances with congenital anomalies at Dr.Sardjito General Hospital in 1998 â 2002. The proportion compared to the whole admittance was 2.06%.The most prevalent was Q35 â Q37 cleft lip and cleft palate (21.14%), followed by Q38 â Q45 othercongenital malformations of the digestive system (18.45%), Q20 â Q28 malformations of the circulatorysystem (15.65%), Q50 â Q56 malformations of genital organs (12,55%), Q00 â Q07 malformations ofthe nervous system (11.89%), Q65-Q79: malformations nd deformations of musculoskeletal system(6.40%), Q80-Q89: other congenital malformations (4.06%), Q10-Q18: malformations of eye, ear, faceand neck (3,91%), Q60-Q64: malformations of the urinary system (2.54%), Q90-Q99: Chromosomalanomalies (2,44%), and Q30-Q34: malformations of the respiratory system (0.97%).Conclusion: Congenital anomalies at Dr. Sardjito General Hospital were dominated by cleft lip and palate,and other congenital malformations of the digestive system. The pattern was similar to that of otherregions of Indonesia, and differed from Indian and European populationsKey words: congenital anomalies â genetic diseases â malformations â Dr. Sardjito General Hospital